Is Conscious Stimulus Identification Dependent on Knowledge of the Perceptual Modality? Testing the “Source Misidentification Hypothesis” - Overgaard, Morten; Lindeløv, Jonas; Svejstrup, Stinna; Døssing, Marianne; Hvid, Tanja; Kauffmann, Oliver; Mouridsen, Kim (Frontiers in Psychology, 2013)
This paper reports an experiment intended to test a particular hypothesis derived from blindsight research, which we name the “source misidentification hypothesis”. According to this hypothesis, a subject may be correct about a stimulus without being correct about how she had access to this knowledge (whether the stimulus was visual, auditory, or something else). We test this hypothesis in healthy subjects, asking them to report whether a masked stimulus was presented auditorily or visually, what the stimulus was, and how clearly they experienced the stimulus using the Perceptual Awareness Scale (PAS). We conclude that knowledge about perceptual modality seems a necessary precondition in order to issue correct reports of which stimulus was presented. Furthermore, we find that PAS ratings correlate with correctness, and that subjects are at chance level when reporting no conscious experience of the stimulus. To demonstrate that particular levels of reporting accuracy are obtained, we employ a statistical strategy, which operationally tests the hypothesis of non-equality, such that the usual rejection of the null-hypothesis admits the conclusion of equivalence.